HIV prevalence, risk, and partner serodiscordance among pregnant women in Bangkok - Wimol Siriwasin (2018)
Context. - Most prior studies of the human immunodeficiency virus (HIV) epidemic in Thailand have focused on commercial sex encounters; however, because the epidemic increasingly concerns stable heterosexual relationships, determining risk factors for this form of transmission is warranted. Objectives. - To determine temporal trends in HIV prevalence, risk factors for HIV seropositivity, and rates of partner serodiscordance for pregnant women in Bangkok, Thailand. Design. - Retrospective review of hospital antenatal clinic HIV test results from 1991 through 1996. Baseline demographic and behavioral risk factors for HIV were assessed for subjects enrolled from November 1992 through March 1994. Setting. - Two Bangkok hospitals with routine antenatal clinic HIV counseling and testing. Participants. - The HIV-positive pregnant women enrolled in a perinatal HIV transmission study and their partners and HIV-negative pregnant controls. Results. - From 1991 through 1996, antenatal clinic HIV seroprevalence increased from 1.0% to 2.3%. On multivariate analysis of data from 342 HIV- positive and 344 HIV-negative pregnant women, more than 1 lifetime sex partner, history of a sexually transmitted disease, and a high-risk sex partner were the most important factors for seropositivity (all P <.001). Twenty-six percent of partners of HIV-positive women were HIV negative. Women reporting more than 1 lifetime sex partner were more likely to have an HIV- negative partner than women reporting only 1 (45% vs 8%; relative risk, 5.5; 95% confidence interval, 3.2-9.5; P < .001); women reporting no high-risk behaviors were less likely to have an HIV-negative partner (10% vs 44%; relative risk, 0.2; 95% confidence interval, 0.1-0.4; P < .001). Conclusions. - Prevalence of HIV in pregnant women has increased steadily in Bangkok from 1991 through 1996. Sex with current partners was the only identified risk exposure for about half (52%) of the HIV-positive women. Although few HIV- positive pregnant women reported high-risk behaviors, more than 1 lifetime partner and a partner with high-risk behavior were strong risk factors for seropositivity. Together with the unexpected finding that one fourth of partners of seropositive pregnant women were seronegative, these data emphasize that women in the general population are at risk for HIV because of the risk behavior of both current and previous partners.